THE ROLE OF MILD COGNITIVE IMPAIRMENT AND SOCIAL ENGAGEMENT IN PREDICTING FALLS AMONG PRIMARY CARE PATIENTS - Quach, L (Innov Aging, 2018)
Mild cognitive impairment (MCI) in older adults, often a precursor to dementia, increases the risk of falls. Relatively little is known whether or how social engagement (SE) mediates the association between MCI and falls. We expect to determine the association between MCI and falls after 2 years, and examine how SE mediates this association. Prospective analysis included 430 community-dwelling older adults at risk of mobility decline with a mean age of 76.6 (range 65 to 96). The number of falls was prospectively collected every three months during two years of follow-up. Key independent variables were measured at a baseline: 1) MCI was identified using a cutoff of 1.5 SD below the age-adjusted mean on a cognitive performance battery; 2) Social engagement (keeping in touch with friends, family, volunteering, and social activities…) was assessed with the Late Life Function and Disability Instrument. High SE required a score above the median value ≥ 49 out of 100. About 49% of participants fell during 2 years, 42% exhibited MCI at the baseline. Generalized Estimating Equation regression indicated that having MCI increased the risk of falls by 59%, adjusting for race, gender, education (IRR=1.59, p<0.008). The association between SE and falls has borderline statistical significance (IRR=0.73, p=0.056). But when SE is added into the models the association between MCI and the rate of falls changes more than 10%. Fall prevention is important among older primary care patients with cognitive impairment. Social engagement needs to be included in designing fall prevention programs for older adults.